Circuit Design for Sensor Detection Signal Conditioner Nitrate Content - Manurung, Robeth Viktoria; Debataraja, Aminuddin; Hiskia, Hiskia (UI Scholars Hub, 2011)
Circuit Design for Sensor Detection Signal Conditioner Nitrate Content. Nitrate is one of macro nutrients very important for agriculture. The availability of nitrate in soil is limited because it is very easy to leaching by rain, therefore nitrate could be contaminated ground water by over-process of fertilizer. This process could also produce inefficiency in agriculture if it happened continuesly without pre-analysis of farm field. The answer those problems, it is need to develop the ion sensor system to measure concentrations of nitrat in soil. The system is consist of nitrate ion sensor device, signal conditioning and data acquisition circuit. The design and fabrications of signal conditioning circuit which integrated into ion nitrate sensor system and will apply for agriculture. This sensor has been used amperometric with three electrodes configuration: working, reference and auxiliarry; the ion senstive membrane has use conductive polymer. The screen printing technique has been choosen to fabricate electrodes and deposition technique for ion sensitive membrane is electropolymerization. The characterization of sensor has been conducted using nitrate standard solution with range of concentration between 1 μM–1 mM. The characterization has shown that sensor has a good response with cureent output between 2.8–4.71 μA, liniearity factor is 99.65% and time response 250 second.